Stabilizing even-parity chiral superconductivity in Sr2RuO4 - Suh, Han Gyeol; Menke, Henri; Brydon, P. M.R.; Timm, Carsten; Ramires, Aline [UNESP]; Agterberg, Daniel F. (American Physical Society (APS), 2020)
Strontium ruthenate (Sr2RuO4) has long been thought to host a spin-triplet chiral p-wave superconducting state. However, the singletlike response observed in recent spin-susceptibility measurements casts serious doubts on this pairing state. Together with the evidence for broken time-reversal symmetry and a jump in the shear modulus c66 at the superconducting transition temperature, the available experiments point towards an even-parity chiral superconductor with kz(kx±iky)-like Eg symmetry, which has consistently been dismissed based on the quasi-two-dimensional electronic structure of Sr2RuO4. Here, we show how the orbital degree of freedom can encode the two-component nature of the Eg order parameter, allowing for a local orbital-antisymmetric spin-triplet state that can be stabilized by on-site Hund's coupling. We find that this exotic Eg state can be energetically stable once a complete, realistic three-dimensional model is considered, within which momentum-dependent spin-orbit coupling terms are key. This state naturally gives rise to Bogoliubov Fermi surfaces.